Development of Corrosion Hazard Map in Peninsular Malaysia Using Inverse Distance Weighting (IDW) Interpolation - Adriyanshah N.F.; Khalid N.H.N.; Usman F.; Izhar A.S.M.; Jawas J.A.; Jalal W.N.W. (Springer Science and Business Media Deutschland GmbH, 2023)
Atmospheric corrosion; Chlorine compounds; Economics; Geographic information systems; Hazards; Interpolation; Sulfur compounds; Corrosion hazard map; Corrosive agents; Economic activities; Extreme weather conditions; Hazard map; Inverse distance weighting; Malaysia; Rust formation; Steel properties; Wet deposition; Corrosion rate